Association Between Transient Elastography and Controlled Attenuated Parameter and Liver Ultrasound in Children With Cystic Fibrosis. Issue 8 (13th May 2021) - Ye, Wen; Leung, Daniel H.; Molleston, Jean P.; Ling, Simon C.; Murray, Karen F.; Nicholas, Jennifer L.; Huang, Suiyuan; Karmazyn, Boaz W.; Harned, Roger K.; Masand, Prakash; Alazraki, Adina L.; Navarro, Oscar M.; et al.
Abstract : Methods to identify children with cystic fibrosis (CF) at risk for development of advanced liver disease are lacking. We aim to determine the association between liver stiffness measurement (LSM) by vibration‐controlled transient elastography (VCTE) with research ultrasound (US) patterns and conventional hepatic markers as a potential means to follow liver disease progression in children with CF. ELASTIC (Longitudinal Assessment of Transient Elastography in CF) is a nested cohort of 141 patients, ages 7‐21, enrolled in the Prediction by US of Risk of Hepatic Cirrhosis in CF (PUSH) Study. We studied the association between LSM with research‐grade US patterns (normal [NL], heterogeneous [HTG], homogeneous [HMG], or nodular [NOD]) and conventional hepatic markers. In a subgroup (n = 79), the association between controlled attenuation parameter (CAP) and US pattern was explored. Among 133 subjects undergoing VCTE, NOD participants (n = 26) had a significantly higher median (interquartile range) LSM of 9.1 kPa (6.3, 15.8) versus NL (n = 72, 5.1 kPa [4.2, 7.0]; P  < 0.0001), HMG (n = 17, 5.9 kPa [5.2, 7.8]; P  = 0.0013), and HTG (n = 18, 6.1 kPa [4.7, 7.0]; P  = 0.0008) participants. HMG participants (n = 14) had a significantly higher mean CAP (SD) (270.5 dB/m [61.1]) compared with NL (n = 40, 218.8 dB/m [46.5]; P  = 0.0027), HTG (n = 10, 218.1 dB/m [60.7]; P  = 0.044), and NOD (n = 15, 222.7 dB/m [56.4]; P  = 0.041) participants. LSM had a negative correlation with platelet count (rs  = ‐ 0.28, P  = 0.0071) and positive correlation with aspartate aminotransferase–to‐platelet ratio index (rs  = 0.38, P  = 0.0002), Fibrosis‐4 index (rs  = 0.36, P  = 0.0007), gamma‐glutamyltransferase (GGT; rs  = 0.35, P  = 0.0017), GGT‐to‐platelet ratio (rs  = 0.35, P  = 0.003), and US spleen size z‐score (rs  = 0.27, P  = 0.0073). Conclusion: VCTE is associated with US patterns and conventional markers in patients with liver disease with CF.